Effect of dietary soybean meal on growth performance, apparent digestibility, intestinal digestive enzyme activity and muscle growth-related gene expression of Litopenaeus vannamei - Peng, Kai; Chen, Xiaoying; Lu, Huijie; Zhao, Jichen; Chen, Yihong; Li, Chaozheng; Li, Huo; Huang, Wen (Frontiers in Marine Science, 2022)
Soybean meal is one of the major components of aquatic animal diets, whereas little information is available about the evaluation of soybean meal growth suppression mode of action. A 42-day feeding trial was performed to assess the effects of dietary soybean meal on growth performance, apparent digestibility, intestinal digestive enzyme activity, and muscle growth–related gene expression of Litopenaeus vannamei. A total of 600 shrimp were randomly distributed into 20 tanks with 30 shrimp per tank and four tanks per group. The soybean meal was added to the diets at the rate of 20% (T20), 28% (T28), 35% (T35), 42% (T42), and 50% (T50), respectively. Shrimp were fed with apparent satiation three times daily. Results indicated that the final body weight, weight gain rate, specific growth rate, feed intake, intestinesomatic index, dressed weight percentage, and the apparent digestibility coefficients of dry matter, crude protein, crude lipid, and ash were linearly decreased (p < 0.05), but feed coefficient was linearly increased (p < 0.05) as dietary soybean meal increased from 20% to 50%. The intestinal trypsin and amylase activities were decreased (p < 0.05) as dietary soybean meal increased from 20% to 50%, and reached significance at the level of 35%, 42%, and 50%. Shrimp fed with T20 had higher (p < 0.05) intestinal lipase activity than those fed with other diets. The mRNA relative expression of growth hormone, myogenic regulatory factor 5, and target of rapamycin was downregulated (p < 0.05) as dietary soybean meal increased from 20% to 50%. To conclude, dietary soybean meal exceeded 28% significantly inhibited growth performance of L. vannamei, mainly due to the negative impact of soybean meal on digestion and feed utilization and also the inhibition on the muscle growth and related gene expressions.